Analysis of CSN2 Exon 7 gene diversity and its association with Sapera goat milk composition - G. Deviandini; R. R. Noor; E. Taufik; S. A. Asmarasari (Diponegoro University, 2023)
Sapera goats, a crossbreed between Saanen and Etawa Grade goats, are known for their milk pro-duction and adaptability to the Indonesian climate. Genetic selection is necessary to improve the Sa-pera goat's milk quality and quantity. CSN2 gene is one of the genes that can affect the composition of goat milk. Therefore, this study aimed to identify the mutation points (SNPs) at the CSN2 exon 7 gene and its association with Sapera goat's milk composition. This study used sixty-six blood and milk sam-ples of Sapera goats collected from the Livestock Research Center, Ciawi. This study found two muta-tion points (SNPs) at g.8946C>T and g.8956G>A. The association analysis showed that SNP g.8946C>T was significantly associated with the lactose and salt content of Sapera goat's milk. In con-clusion, SNP g.8946C>T can be used as a genetic marker to improve the composition of Sapera goat milk with high lactose and salt content.